Risk-adapted stereotactic ablative radiotherapy for central and ultra-central lung tumours. (May 2019) - Lenglet, Alexis; Campeau, Marie-Pierre; Mathieu, Dominique; Bahig, Houda; Lambert, Louise; Vu, Toni; Roberge, David; Bilodeau, Laurent; Filion, Edith
Highlights: Central tumours have a better median overall survival than ultra-central tumours. Local control is not different between central and ultra-central tumours. No difference of toxicity was observed between central and ultra-central tumours. Cumulative incidence of grade 3–5 toxicity events was 7%. Abstract: Background: SABR is a widely accepted treatment for early-stage lung cancer but there are safety concerns for central and ultra-central tumours. Herein we report our experience using risk-adapted fractionation (prescribed doses: 40–60 Gy in 3–8 fractions) with prioritization of dose to organs at risk. Methods: Patient declining or unsuitable for surgery with primitive or recurrent lung cancer were included. Tumours inside a 2 cm area around proximal bronchial tree (PBT) were classified as central while tumours with PTV overlapping PBT, oesophagus, great vessels and pericardial pleura were classified as ultra-central. We assessed overall survival (OS), disease-free survival (DFS), local control (LC) and toxicities. Results: From 2009 to 2016, 137 patients were treated (median age: 75 years), with 60 central and 77 ultra-central tumours. Median follow-up was 36 months. Median tumour size, GTV and PTV were 2.5 cm (0.9–7), 7.8 cm 3 (0.7–94.2) and 30.6 cm 3 (6.5–274.3), respectively. For the whole population, median OS and DFS were 46 months and 33 months. One- and 2-years LC rates were 95% and 81%. Median OS between central and ultra-central tumours was statistically different with 57 vs 37 months (HR 0.48, p  = 0.017), but LC was not different among them. We observed 4 Grade 3 and 6 Grade 5 toxicities (no grade 4). Conclusions: SABR for central and ultra-central tumours is associated with good OS, DFS and LC rates, with 7.3% grade 3–5 toxicities. Central tumours had a better prognosis in our cohort.